The maturation of faith. An outline of the development Church’s consciousness of faith’s truths in the lens of Gospel prophecy - Polak, Krzysztof (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
„I have much more to say to you, more than you can now bear. But when he, the Spirit of Truth, comes, he will guide you into all the truth.” (John 16, 12-13a) Due to the limited capabilities of the human mind, Jesus conveyed the fullness of the revealed truth, but in embryonic shape. Therefore, he announced that only in the future would the truth be revealed and fully explored - with the help of the Spirit of Truth. The history of the Church, and especially the history of deepening the understanding of faith, is a process in which the prophecy of the Gospel of John is being realized. In the centuries of the first millennium, councils have solemnly defined the main truths of the Christian faith that are unanimously confessed by all Christians. For many centuries, faith in the Church, as a secondary truth to the main articles of faith contained in the Creed, was described imperfectly and partially, which aroused objections. Especially in modern times, after the Reformation, controversies have intensified regarding the understanding of the Church. It was only in the second half of the 20th century, during the Second Vatican Council (1962-1965), that plentiful teaching about the Church was formulated, which overcame the previous defects. The teaching of Lumen Gentium, the main document of the council, is free from polemics and condemnations, and does not contain any traces of fear of the numerous threats coming from the world of the second half of the 20th century - a century of totalitarianisms, wars, and revolutions that claimed millions of victims. It expresses the calm certainty of faith that it is enough to faithfully read God's intentions towards the Church, submit to them to re-illuminate the Church with the saving splendor of the Gospel. With such certainty of faith, the Fathers of the Council renewed the image of the Church, cleansed it from previous defects and they did so drawing from biblical sources and tradition.